Building a Model of Suitable Performance Management Framework - Reno Renaldi Tibyan; Dermawan Wibisono; Mursyid Hasan Basri (International Journal of Supply Chain Management, 2019)
This paper aims to develop a conceptual performance management framework and a theoretical model to determine a suitable performance management framework. The study uses a systematic approach to determine an appropriate performance management framework, which encompasses the process of identifying issues related to performance management, conducting a thorough literature review, identifying gaps through comparing and contrasting the performance management frameworks, identifying theorised constructs, developing a conceptual framework, and building a theoretical model. The results of this study suggest that the proposed conceptual performance management framework applies an input-process-output-outcome model to indicate performance measurement as part of performance management and to describe a complete process of transforming performance measures data into reliable performance information. Five suggested factors to determine a suitable performance management framework have been identified in a developed theoretical model, which include a useful method for modelling a system, management control tool, framework applicability, performance measurement, and practical guidelines for performance management system. This study identifies and suggests five criteria for determining a suitable performance management framework. Other aspects can be included to develop more robust criteria. Theoretical verification needs to be undertaken to examine the conceptual variables of the proposed framework. The developed theoretical model is subject to empirical testing. This study encourages performance management research concerning a thorough process of developing performance management framework and establishing criteria and a model to determine a suitable performance management framework.